KEBIJAKAN IPTEK, JENDER DAN HAM DI INDONESIA - Tri Lisiani Prihatina (Masalah-Masalah Hukum, 2010)
Science is the study of nature and behaviour including the reasons why less women interested in science. Not only they have to face an internal problem, but also they face an external problem. this paper demonstrates that women rights on science have already been accomodated in some Educational Regulations, although there are some problems with those regulations which give more focus on economic functions instead of educating people. Therefore, the people with more economic capability will have more access on education including the science. Besides, those regulations are symmetry with some regulations of Intellectual Property. Feminists suggest to change technological regulation from masculine technology to feminime technology as they believe feminine technology will give women more educational access.Kata Kunci : perempuan, IPTEK, HAM